Production of Carotenoids and Phospholipids by Thraustochytrium sp. in Batch and Repeated-Batch Culture - Allison Leyton; Carolina Shene; Yusuf Chisti; Juan A. Asenjo (Marine Drugs, 2022)
The carotenogenic thraustochytrid Thraustochytrium sp. RT2316-16 was grown in batch and repeated-batch cultures using different feeds containing glucose, or glycerol, and yeast extract, for the production of lipids, phospholipids and carotenoids. RT2316-16 produced canthaxanthin, astaxanthin and β-carotene. The effects of biotin, ascorbic acid, light and temperature were evaluated in some of the experiments. In 2-day-old batch cultures, the combined mass percentage of eicosapentaenoic acid and docosahexaenoic acid in total lipids was between 16.5% (glycerol-based medium in the dark; biomass concentration = 4.2 ± 1.1 g L−1) and 42.6% (glucose-based medium under light; biomass concentration = 3.3 ± 0.1 g L−1), decreasing to 3.8% and 6.1%, respectively, after day 4. In repeated-batch cultures, the total lipids in the biomass increased after glucose or glycerol was fed alone, whereas the total carotenoids (168 ± 7 μg g−1 dry weight (DW)) and phospholipids in the biomass increased after feeding with yeast extract. The biomass with the highest content of phospholipids (28.7 ± 4.3 mg g−1 DW) was obtained using a feed medium formulated with glycerol, yeast extract and ascorbic acid. Glycerol was the best carbon source for the production of a biomass enriched with total lipids (467 ± 45 mg g−1 DW). The composition of carotenoids depended strongly on the composition of the feed. Repeated-batch cultures fed with yeast extract contained canthaxanthin as the main carotenoid, whereas in the cultures fed only with glucose, the biomass contained mainly β-carotene.